The underlying reasons for the slow gender transformation of black African female senior managers in the private sector - Gonono, Yolanda (My University, 2020)
This study looks into the internal issues within the private sector that are possibly the reason for the slow rate of gender transformation. The annual Employment Equity Report (2017) by the Department of Labour shows that gender transformation is moving at a slow pace, particularly for black African females in senior management positions. The research sample is made up of black African female senior managers and HR staff in the telecoms, looking at their personal experiences. The research findings show that gender transformation is multifaceted and employment equity on its own will not produce the desired results. There are initiatives to empower women and progressive legislature but there is an apparent resistance for gender transformation in the workforce. These internal issues’ root cause is the lack of change in systems and culture of the workforce, which was previously created for men and women are still having to change themselves to fit into it
Research report submitted to the Faculty of Humanities, School of Social Sciences, University of the Witwatersrand, in partial fulfilment of the requirements for the award of the degree of Master of Arts